TypeScript : modern JavaScript development : leverage the features of TypeScript to boost your development skills and create captivating applications : a course in three modules. - Jansen, Remo H.; Vane, Vilic; Wolff, Ivo Gabe de (Packt Publishing, 2016)
Leverage the features of TypeScript to boost your development skills and create captivating applications About This Book Learn how to develop modular, scalable, maintainable, and adaptable web applications by taking advantage of TypeScript Explore techniques to use TypeScript alongside other leading tools such as Angular 2, React, and Node.js Focusing on design patterns in TypeScript, this step-by-step guide demonstrates all the important design patterns in practice Who This Book Is For This Learning Path is for intermediate-level JavaScript developers who want to use TypeScript to build beautiful web applications and fun projects. No prior knowledge of TypeScript is required, but a basic understanding of jQuery is expected. This Learning Path is also for experienced TypeScript developers who want to take their skills to the next level, and also for web developers who wish to make the most of TypeScript. What You Will Learn Understand the key TypeScript language features and runtime Install and configure the necessary tools in order to start developing an application Create object-oriented code that adheres to the SOLID principles Develop robust applications with testing (Mocha, Chai, and SinonJS) Apply GoF patterns in an application with a testing approach Identify the challenges when developing an application Migrate JavaScript codebases to TypeScript to improve your workflow Utilize System.JS and Webpack to load scripts and their dependencies Develop high performance server-side applications to run within Node.js In Detail TypeScript is an open source and cross-platform typed superset of JavaScript that compiles to plain JavaScript that runs in any browser or any host. TypeScript adds optional static types, classes, and modules to JavaScript, to enable great tooling and better structuring of large JavaScript applications. Through this three-module learning path, you'll learn the ins-and-outs of TypeScript for building more robust software. The first module gets you started with TypeScript and helps you understand the basics of TypeScript and automation tools. Get a detailed description of function, generics, callbacks, and promises, and discover the object-oriented features and memory management functionality of TypeScript. The next module starts by explaining the current challenges when designing and developing an application and how you can solve these challenges by applying the correct design pattern and best practices. You will be intro...